Bead foam molded products and cushioning materials

JP2026166797APending Publication Date: 2026-10-14SEKISUI PLASTICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059984
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、ポリエステル系エラストマー発泡粒子で構成されたビーズ発泡成形体において優れた軽量性と強度と反発弾性とを兼ね備えさせ得るとともに、軽量性と強度と反発弾性とに優れた緩衝材が提供され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166797000001_ABST
    Figure 2026166797000001_ABST
Patent Text Reader

Abstract

This invention provides a bead-foamed molded body that is composed of polyester elastomer foam particles while possessing lightweight properties, excellent strength, and rebound elasticity. [Solution] A foamed bead molded body composed of multiple foamed resin particles fused to each other, wherein the foamed resin particles are made of a resin composition containing a polyester elastomer, and the density is 200 kg / m³ 3 The following provides a bead foam molded article having a rebound modulus of 70% or more and a tear strength of 2.0 N / mm or more, wherein when the temperature dependence of the storage modulus is represented on a semi-logarithmic graph with the vertical axis being a logarithmic scale of storage modulus (Pa) and the horizontal axis being temperature (°C), the decrease in storage modulus per unit temperature is 0.06 or more at a first temperature (T1) between 120°C and 140°C, the decrease returns to 0.06 or less at a second temperature (T2) between 140°C and 170°C, and the temperature difference between T1 and T2 (ΔT(T2-T1)) is greater than 17°C and less than or equal to 35°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a bead foam molded body and a cushioning material. [Background technology]

[0002] Traditionally, foamed molded products made of polystyrene resin, often referred to as expanded polystyrene, have been widely used as insulated containers for transporting fresh foods such as vegetables and seafood due to their lightweight nature and excellent heat insulation properties. This type of foamed molded product is manufactured by heating foamed resin particles filled into a mold with superheated steam to fuse the particles together, and is sometimes referred to as a beaded foamed molded product.

[0003] In recent years, foamed bead molded products made from resins other than polystyrene resin have also come to be used in industrial products. Patent Document 1 below describes the production of foamed molded products that can be used as cushioning materials, etc., using polyester elastomer foam particles formed from a resin composition containing a polyester elastomer in order to form a foamed molded product that is low in density and exhibits high rebound elasticity. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] International Publication No. 2018 / 012089 [Overview of the project] [Problems that the invention aims to solve]

[0005] In bead foam molded articles, sufficient fusion between foam resin particles is desirable for excellent strength to be achieved. As shown in Table 1 (paragraph 0054) of the above-mentioned Patent Document 1, when attempting to achieve high rebound elasticity in a bead foam molded article composed of polyester elastomer foam particles, the fusion rate becomes low, making it difficult to achieve both lightness and excellent strength and rebound elasticity in a bead foam molded article composed of polyester elastomer foam particles. Therefore, it is difficult to form a cushioning material that is lightweight yet has excellent strength and rebound elasticity using polyester elastomer. Accordingly, the present invention aims to provide a bead foam molded article that is lightweight while possessing excellent strength and rebound elasticity, and to provide a cushioning material made of polyester elastomer that is lightweight, strong, and has excellent rebound elasticity. [Means for solving the problem]

[0006] The present invention, which solves the above problems, It is composed of multiple foamed resin particles that are fused together with each other. A bead foam molded article in which the foamed resin particles are polyester elastomer foam particles composed of a resin composition containing a polyester elastomer, Density is 200 kg / m³ 3 Below, With a rebound modulus of 70% or more, The tear strength is 2.0 N / mm or higher. The aforementioned resin composition, The present invention provides a bead foam molded article in which, when the temperature dependence of the storage modulus is represented on a semi-logarithmic graph with the vertical axis representing the storage modulus (Pa) on a logarithmic scale and the horizontal axis representing temperature (°C), the decrease in the storage modulus per unit temperature is 0.06 or more at a first temperature (T1) between 120°C and 140°C, the decrease in the storage modulus per unit temperature returns to 0.06 or less at a second temperature (T2) between 140°C and 170°C, and the temperature difference (ΔT(T2-T1)) between the first temperature (T1) and the second temperature (T2) is greater than 17°C and less than or equal to 35°C.

[0007] The present invention for solving the above problems is, A cushioning material at least a part of which is formed of a bead foam molded article, Provided is a cushioning material, wherein the bead foam molded article is the bead foam molded article as described above.

Effects of the Invention

[0008] According to the present invention, it is possible to impart excellent lightweight properties, strength and impact resilience to a bead foam molded article composed of polyester-based elastomer expanded particles, and to provide a cushioning material excellent in lightweight properties, strength and impact resilience.

Brief Description of the Drawings

[0009] [Figure 1] Figure 1 is a semilogarithmic graph showing the relationship between temperature and storage elastic modulus in an example of the resin composition constituting the bead foam molded article. [Figure 2a] Figure 2a is a schematic view showing the shape of a test piece for measuring the tear strength of the bead foam molded article. [Figure 2b] Figure 2b is a schematic view showing a test method for measuring the tear strength of the bead foam molded article. [Figure 3] Figure 3 is a semilogarithmic graph showing the comparison of the relationship between the temperature and the storage elastic modulus of the resin compositions constituting the bead foam molded articles of Example 1 and Comparative Example 1.

Modes for Carrying Out the Invention

[0010] Embodiments of the present invention will be described below. The foamed molded body in this embodiment is a bead foamed molded body, and is composed of a plurality of foamed resin particles that are fused to each other. The foamed resin particles constituting the bead foamed molded body in this embodiment are polyester elastomer foamed particles composed of a resin composition containing a polyester elastomer. The polyester elastomer foamed particles contain a plurality of air bubbles, and a plurality of cells are formed inside, partitioned by a thin film (hereinafter also referred to as "air bubble film") made of the resin composition.

[0011] The resin composition constituting the polyester elastomer foam particles comprises a resin component containing a polyester elastomer as an essential component, and may further contain additives as optional components.

[0012] The bead foam molded article of this embodiment is composed of a resin composition that exhibits a unique change in storage modulus when heated. Figure 1 shows a change curve CV representing the temperature dependence of the storage modulus of the resin composition on a semi-logarithmic graph where the vertical axis is on a logarithmic scale of storage modulus (Pa) and the horizontal axis is on temperature (°C). In the change curve CV of the storage modulus of the resin composition constituting the bead foam molded article, as shown in Figure 1, the storage modulus decreases as the temperature rises, and moreover, the storage modulus decreases in a step-like manner. That is, the step portion of the change curve CV, which is a step-like curve, represents a situation where the storage modulus decreases significantly compared to the preceding or following portion.

[0013] More specifically, the change curve CV in this embodiment includes a high-decrease section CV1 where the decrease in storage modulus per unit temperature is 0.06 or more, and between the high-decrease section CV1, there are low-decrease sections CV2 on the low-temperature side and high-temperature side of the high-decrease section CV1, where the decrease in storage modulus per unit temperature is less than 0.06. That is, the change curve CV has a first change point where, when the decrease in storage modulus per unit temperature is observed from the low-temperature side to the high-temperature side, the absolute value of the decrease increases to 0.06 or more, which is at the boundary between the first low-decrease section CV21, which is the low-decrease section CV2 on the lower temperature side of the high-decrease section CV1, and the high-decrease section CV1. A second change point where the absolute value of the decrease in storage modulus per unit temperature, which was 0.06 or more at the boundary point, returns to 0.06 or less, is at the boundary point between the second low-decrease section CV22, which is the low-decrease section CV2 on the higher temperature side of the high-decrease section CV1, and the high-decrease section CV1. In this embodiment, the temperature indicating the second change point is located at a certain temperature higher than the temperature indicating the first change point.

[0014] In this embodiment, when the resin composition constituting the bead foam molded body has a first temperature (T1:°C) at which the first change point occurs and a second temperature (T2:°C) at which the second change point occurs, the fact that both the first temperature (T1:°C) and the second temperature (T2:°C) are above a certain temperature means that interactions are occurring between the molecules of the polyester elastomer contained in the resin composition, and relatively high intermolecular forces are acting. It is believed that this is what causes the bead foam molded body of this embodiment to exhibit excellent rebound elasticity. However, as the temperature of the first temperature (T1:°C) and the second temperature (T2:°C) increases, the heating temperature when producing the bead foam molded body will also increase, and raising these temperatures to an unnecessarily high temperature may make it difficult to achieve good molding. Therefore, it is preferable that these temperatures remain within a certain range. Furthermore, a certain level of difference between the first temperature (T1:°C) and the second temperature (T2:°C) means that the polyester elastomer foam particles are suppressed from changing excessively with temperature, making it easier to avoid problems such as heat shrinkage during molding. However, if these temperature differences are made unnecessarily large, it would be necessary to lower the first temperature (T1:°C) or raise the second temperature (T2:°C), and it is preferable that these temperature differences are not excessively large in order to ensure good moldability.

[0015] The resin composition constituting the bead foam molded body of this embodiment satisfies all of the following formulas (1), (2), and (3) at the first temperature (T1:°C) and the second temperature (T2:°C). 120℃ ≦ T1 ≦ 140℃ (1) 140℃ ≦ T2 ≦ 170℃ (2) 17℃ < (T2-T1) ≦35℃ ···(3)

[0016] By making the first temperature (T1: °C) and the second temperature (T2: °C) satisfy the above relationship, in the present embodiment, the polyester-based elastomer expanded particles can exhibit good foamability and fusion bonding property, and the bead expanded molded article can be made excellent in lightweight property, strength and impact resilience.

[0017] (Density) The bead expanded molded article has, for example, a density of 200 kg / m 3 or less. The density of the bead expanded molded article may be, for example, 180 kg / m 3 or less, may be 160 kg / m 3 or less, may be 140 kg / m 3 or less, may be 120 kg / m 3 or less, may be 100 kg / m 3 or less.

[0018] (Method for Determining Density) The density of the bead expanded molded article can be measured by the method described in JIS K7222:2005 "Foamed plastics and rubbers - Determination of apparent density". That is, a test piece of 50 mm × 50 mm × 10 mm is sampled from the bead expanded molded article so as not to change the original cell structure of the material as much as possible, the mass thereof is measured, and the density is calculated by the following formula. Density (kg / m 3 ) = Mass of test piece (g) / Volume of test piece (mm 3 ) × 10 6 In principle, the test piece for measurement is cut out from the bead expanded molded article that has passed 72 hours or more after molding, and is left to stand in an atmosphere condition of a temperature of 23 ± 2 °C and a humidity of 50 ± 5% for 16 hours or more for measurement.

[0019] (Impact Resilience Rate) The bead expanded molded article of the present embodiment exhibits an excellent impact resilience rate. The impact resilience rate of the bead expanded molded article can be, for example, 70% or more. The impact resilience rate may be 71% or more, or 72% or more. The impact resilience rate means the ratio of the rebound height when a metal ball is freely dropped onto the bead expanded molded article from a position of a predetermined height.

[0020] (How to calculate the modulus of resilience) In this embodiment, the rebound modulus is measured in accordance with JIS K6400-3:2011 "Test Method for Flexible Polyurethane Foam". Specifically, the rebound modulus is measured by Method A described in the same standard. A "Rebound Modulus Tester FR-1" manufactured by Polymer Instruments Co., Ltd. is used for the measurement. The test piece is 100 mm square and 50 mm thick. A steel ball of nominal size 16 mm, grade G40 (diameter 16 ± 0.5 mm, mass 16.8 ± 1.5 g) as specified in JIS B1501 is used for the measurement. The rebound modulus is calculated by the following formula. However, the ball drop distance is assumed to be 500 mm. Rebound modulus (%) = Maximum rebound distance (mm) / Drop distance (500mm) × 100 (%) The test specimens were conditioned for 16 hours under a standard atmosphere of Class 2, symbol "23 / 50" according to JIS K7100:1999, before being used for measurement, and the measurement was performed under the same environment.

[0021] (Fusion rate) The bead foam molded body is preferably manufactured to have a fusion rate of 50% or more. More preferably, the fusion rate of the bead foam molded body is 70% or more, and even more preferably 80% or more.

[0022] (How to calculate the fusion rate) The fusion rate of a bead foam molded body is determined by making a cut approximately 5 mm deep along a straight line connecting the centers of a pair of long sides on the surface of the bead foam molded body (400 mm x 300 mm x 20 mm thick) using a utility knife, and then dividing the bead foam molded body into two along this cut line. For the foam resin particles on the fracture surface of the two divided bead foam molded bodies, an arbitrary range containing 100 polyester elastomer foam particles is set, and within this range, the number of polyester elastomer foam particles that have fractured within the polyester elastomer foam particles (a) and the number of polyester elastomer foam particles that have fractured at the interface between polyester elastomer foam particles (b) are counted, and the fusion rate F (%) is calculated using the following formula. F(%) = a / (a+b) × 100(%)

[0023] (tear strength) The bead foam molded article of this embodiment has a tear strength of 2.0 N / mm or more. The tear strength of the bead foam molded article may be, for example, 2.1 N / mm or more, 2.2 N / mm or more, 2.3 N / mm or more, or 2.4 N / mm or more. The tear strength of the bead foam molded article may be, for example, 5.0 N / mm or less.

[0024] (How to determine tear strength) Tear strength will be measured using the Shimadzu Corporation's "Autograph AG-X plus 100kN" universal testing machine and the Shimadzu Corporation's "TRAPEZIUM X" universal testing machine data processing. The test specimens will be cut from the bead foam molded body to the shape shown in Figure 2a (square bar shape with a width of 25 mm, a length of 150 mm, and a thickness of 20 mm), and a cut will be made through the center in the thickness direction at a interval of 40 mm from one end in the length direction. Five test specimens will be prepared. The test specimens will be conditioned for 16 hours or more under a standard atmosphere of JIS K7000:1999 symbol "23 / 50" and class 2 before being used for measurement. The measurement is performed under the same environmental conditions. As shown by the block arrow in Figure 2b, the notched portion is opened vertically and set in the grips of the universal testing machine. The test speed is 100 mm / min, and the grip spacing before the start of the test is 50 mm. A load is applied vertically so that the notch tears, and the point at which the test piece separates is considered the endpoint. The tear strength is calculated in accordance with ISO 6133:2015 using the data processing of the universal testing machine described above.

[0025] (Asker C hardness) The bead foam molded body may have an Asker C hardness of 40 or less. Having an Asker C hardness of 40 or less makes the bead foam molded body suitable as a component for cushioning materials and the like. The Asker C hardness of the bead foam molded body may be 39 or less, 38 or less, or 37 or less. The lower limit of the Asker C hardness can be, for example, 20.

[0026] (How to determine Asker C hardness) The Asker C hardness of a bead foam molded body is determined by conditioned a 50mm x 50mm x 20mm thick sample for at least 72 hours at a temperature of 23±2°C and a humidity of 50±5%, and then measured using a hardness tester (Asker Rubber & Plastic Hardness Tester Type C, manufactured by Polymer Instruments Co., Ltd.). During measurement, the pressure surface is pressed firmly against the test piece so that the indenter is perpendicular to the measurement surface, and the scale is read immediately. Then, avoiding the fused surfaces of the polyester elastomer foam particles, five points on the sample are measured, and the average value is taken as the Asker C hardness.

[0027] In this embodiment, the bead foam molded article uses a resin composition in which the first temperature (T1:°C) and the second temperature (T2:°C) have a predetermined relationship. Therefore, it is easy to achieve the excellent rebound modulus and excellent tear strength described above, even at a low density.

[0028] To ensure that these functions are performed more reliably, the first temperature (T1:°C) is preferably 123°C to 138°C, more preferably 124°C to 137°C, even more preferably 125°C to 136°C, and particularly preferably 125°C to 133°C. The second temperature (T2:°C) is preferably 143°C to 167°C, more preferably 145°C to 164°C, even more preferably 147°C to 160°C, and particularly preferably 147°C to 155°C. The temperature difference between these two temperatures (ΔT=T2-T1) is preferably 18°C ​​to 30°C, and more preferably 20°C to 25°C.

[0029] (How to find the first and second temperatures) The first temperature (T1:°C) and the second temperature (T2:°C) of the resin composition can be determined by measuring the dynamic viscoelasticity as follows. (Method for measuring dynamic viscoelasticity) Dynamic viscoelasticity measurements are performed using an Anton Paar "PHYSICA MCR301" viscoelasticity analyzer and "CTD450" temperature control system. First, a disc-shaped sample with a diameter of 25 mm and a thickness of 3 mm is prepared by compression molding of the bead foam into a non-foamed state at a temperature of 200°C using a hot press. Next, the sample is placed on the plate of the viscoelasticity analyzer heated to the measurement start temperature of 220°C. The sample is heated and melted in a nitrogen atmosphere for 5 minutes. After that, the sample is crushed from above with a 25 mm diameter parallel plate. The sample is crushed until the gap between the plates is 2.0 mm. Then, the resin that has overflowed from the plate is removed. After the instrument temperature reaches the measurement start temperature of 220 ± 1°C, it is heated for another 5 minutes. After that, dynamic viscoelasticity measurements are performed to measure the storage modulus and loss modulus in the range of 50 to 220°C. The measurement conditions are as follows. Distortion: 0.025% Frequency: 1Hz Cooling rate: 2℃ / min Measurement interval: 30 seconds Normal Force: ON

[0030] At this time, the molten sample is cooled at a rate of 2°C / min from the starting temperature, and the storage modulus (G') is measured every 30 seconds. Next, the natural logarithm (X) (=log) of this storage modulus (G') is measured. 10 Calculate G') for each measurement point. Then, calculate the natural logarithm (X) of the i-th measurement point from the start of the cooling down. i ) and the natural logarithm of the next measurement point ((i+1)th) (X i+1 ) difference (ΔX i )(=X i+1 -X i ) is calculated, the value is rounded to the third decimal place, and the difference value to the second decimal place (decrease in storage modulus per unit temperature: ΔX') is obtained. i ) is calculated. Then, the difference value at the i-th (decrease in storage modulus per unit temperature: ΔX') is calculated. i ) is less than 0.06 and the difference value at the (i+1)th position (decrease in storage modulus per unit temperature: ΔX') i+1Find the boundary where ) is 0.06 or greater, and set the temperature at this i-th measurement point as the second temperature (T2). Similarly, the difference value at the j-th (j>i) point (decrease in storage modulus per unit temperature: ΔX') is determined. j+1 ) is 0.06 or greater and the difference value at the (j+1)th position (decrease in storage modulus per unit temperature: ΔX') j+1 The boundary at which the value becomes less than 0.06 is determined on the lower side of the second temperature (T2), and the temperature of this j-th measurement point is taken as the first temperature (T1).

[0031] The polyester elastomer in this embodiment is a polymer containing both a hard segment and a soft segment within a single molecule. The temperature characteristics described above can be achieved by adjusting the ratio of the hard segment to the soft segment of the polyester elastomer and the copolymer components.

[0032] The hard segment is, for example, an aromatic polyester. The aromatic polyester can be, for example, a condensation polymer of a dicarboxylic acid component and a diol component, and at least one of the dicarboxylic acid component and the diol component can be an aromatic compound. The aromatic polyester does not need to consist of only one type of dicarboxylic acid component and one type of diol component; each may consist of one or more types. Furthermore, the aromatic polyester may contain, in trace amounts (e.g., 5 mol% or less), structural units derived from components copolymerizable with the dicarboxylic acid component and the diol component, in addition to the dicarboxylic acid component and the diol component. That is, the aromatic polyester may be a multi-component polymer containing three or more types of structural units.

[0033] The soft segment includes polyester and / or polyether. Examples of polyester-type soft segments include dicarboxylic acids (aliphatic C such as adipic acid). 4-12 Dicarboxylic acids and diols (such as 1,4-butanediol) 2-10 (Poly)oxyC such as alkylene glycol and ethylene glycol 2-10 Polycondensates with alkylene glycols, polycondensates of oxycarboxylic acids, and lactones (such as ε-caprolactone).3-12 Examples include aliphatic polyesters such as ring-opening polymers of lactones. The polyester type soft segment may be amorphous. Specific examples of polyesters as soft segments include caprolactone polymers, polyethylene adipate, polybutylene adipate, etc. 2-6 Alkylene glycol and C 6-12 Polyesters with alkanedicarboxylic acids are examples. The number-average molecular weight of these polyesters may be in the range of 200 to 15000, 200 to 10000, or 300 to 8000. The lower and upper limits of the number-average molecular weight range can be 200, 300, 500, 1000, 3000, 5000, 8000, 10000, 12000, and 15000, respectively.

[0034] Examples of polyether-type soft segments include segments derived from aliphatic polyethers such as polyalkylene glycols (e.g., polyoxyethylene glycol, polyoxypropylene glycol, polyoxytetramethylene glycol). The number-average molecular weight of the polyether may be in the range of 200 to 10000, 200 to 6000, or 300 to 5000. The lower and upper limits of the number-average molecular weight range can be 200, 300, 500, 1000, 2000, 4000, 5000, 6000, 8000, and 10000, respectively.

[0035] The soft segment may be derived from a polyester having polyether units, such as a copolymer of an aliphatic polyester and a polyether (polyether-polyester), or from a polyester of a polyether and an aliphatic dicarboxylic acid, such as polyoxyalkylene glycol (e.g., polyoxytetramethylene glycol).

[0036] The hard segment and the soft segment, or both, may be petroleum-derived compounds or plant-derived compounds made from biomass such as corn or sugarcane. That is, the polyester elastomer may be a polyester elastomer in which some or all of its constituent units are plant-derived. The plant-derived polyester elastomer may have a biomass content of 10% or more, 15% or more, 20% or more, 25% or more, 50% or more, or 100%. The biomass content is C 14 It can be determined based on this.

[0037] The mass ratio of the hard segment to the soft segment may be 20:80 to 90:10, 30:70 to 90:10, 30:70 to 80:20, 40:60 to 80:20, or 40:60 to 75:25. The lower and upper limits of the mass ratio range can be 20:80, 25:75, 30:70, 40:60, 50:50, 60:40, 70:30, 75:25, 80:20, and 90:10.

[0038] The resin composition and one or more polyester elastomers contained in the resin composition may have a melting point of, for example, 100 to 200°C. A melting point of 200°C or lower facilitates softening during foaming, making it easier to obtain low-density bead-foamed molded articles. A melting point of 100°C or higher reduces the likelihood of shrinkage after the pre-foaming process, thus suppressing the risk of difficulties in molding. The melting point of the resin composition and polyester elastomer may be 120 to 200°C or 120 to 190°C. The lower and upper limits of the melting point range may be any of the following values, respectively: 100°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, and 200°C.

[0039] The melting point of polyester elastomers can be determined using a differential scanning calorimetry (DSC) as the peak temperature of the endothermic curve due to melting when heated at a constant heating rate (e.g., 10°C / min).

[0040] One or more polyester elastomers contained in the resin composition may have, for example, a crystallization heat (qc: mJ / mg) greater than 0 mJ / mg and less than or equal to 30 mJ / mg. The crystallization heat may be 3 to 30 mJ / mg, 6 to 30 mJ / mg, or 9 to 30 mJ / mg. The lower and upper limits of the crystallization heat range may be any of the following values, respectively: 2 mJ / mg, 3 mJ / mg, 6 mJ / mg, 9 mJ / mg, 10 mJ / mg, 15 mJ / mg, 20 mJ / mg, 25 mJ / mg, and 30 mJ / mg.

[0041] In order to achieve the effects described above, it is preferable that the resin composition contains multiple polyester elastomers, including a first polyester elastomer and a second polyester elastomer. More specifically, it is preferable that the resin composition contains multiple polyester elastomers, including a first polyester elastomer which is the main component of the resin component of the resin composition and a second polyester elastomer which is a minor component. In this embodiment, the resin composition contains multiple polyester elastomers, taking into account that the second temperature (T2) and the first temperature (T1) of one polyester elastomer increase when another polyester elastomer is added, and the temperature difference between them (ΔT=T2-T1) also increases.

[0042] The first polyester elastomer, which is the main component of the resin, is present in proportion to the resin component, for example, 60% by mass or more. The second polyester elastomer, which is a secondary component of the resin, is present in proportion to the resin component, for example, 1% by mass or more and 40% by mass or less.

[0043] The first polyester elastomer, which is the main component of the resin, preferably has a first temperature (T1:°C) of 110°C or higher. The first temperature (T1:°C) of the first polyester elastomer may be, for example, 115°C or higher, 120°C or higher, or 125°C or higher. The first temperature (T1:°C) of the first polyester elastomer may be, for example, 140°C or lower. The first temperature (T1:°C) of the first polyester elastomer may be, for example, 135°C or lower, or 130°C or lower.

[0044] The first polyester elastomer preferably has a second temperature (T2:°C) of 125°C or higher. The first temperature (T2:°C) of the first polyester elastomer may be, for example, 130°C or higher, 135°C or higher, or 140°C or higher. The first temperature (T2:°C) of the first polyester elastomer may be, for example, 160°C or lower. The first temperature (T2:°C) of the first polyester elastomer may be, for example, 155°C or lower, or 150°C or lower.

[0045] The first polyester elastomer preferably has a temperature difference (ΔT':T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of 13°C or higher. The temperature difference (ΔT':T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of the first polyester elastomer may be, for example, 14°C or higher, or 15°C or higher. The temperature difference (ΔT':T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of the first polyester elastomer may be, for example, 20°C or lower. The temperature difference (ΔT':T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of the first polyester elastomer may be, for example, 19°C or lower, or 18°C ​​or lower.

[0046] The first polyester elastomer preferably has a hard segment content of 35% to 50% by mass. The first polyester elastomer preferably has a crystallization temperature of 80°C to 100°C and a crystallization heat of 15 mJ / mg to 25 mJ / mg. The first polyester elastomer may be a plant-derived polyester elastomer or a petroleum-derived polyester elastomer.

[0047] The second polyester elastomer, which is a minor component of the resin component, preferably has a first temperature (T1:°C) of 90°C or higher. The first temperature (T1:°C) of the second polyester elastomer may be, for example, 95°C or higher, 100°C or higher, or 105°C or higher. The first temperature (T1:°C) of the second polyester elastomer may be, for example, 140°C or lower. The first temperature (T1:°C) of the first polyester elastomer may be, for example, 135°C or lower, or 130°C or lower.

[0048] The second polyester elastomer preferably has a second temperature (T2:°C) of 110°C or higher. The second temperature (T2:°C) of the second polyester elastomer may be, for example, 115°C or higher, or 120°C or higher. The second temperature (T2:°C) of the second polyester elastomer may be, for example, 140°C or lower. The second temperature (T2:°C) of the second polyester elastomer may be, for example, 135°C or lower, or 130°C or lower.

[0049] The second polyester elastomer preferably has a temperature difference (ΔT”:T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of 10°C or more. The temperature difference (ΔT”:T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of the second polyester elastomer may be, for example, 11°C or more, or 12°C or more. The temperature difference (ΔT”:T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of the second polyester elastomer may be, for example, 17°C or less. The temperature difference (ΔT”:T2-T1) between the second temperature (T2:°C) and the first temperature (T1:°C) of the second polyester elastomer may be, for example, 16°C or less, or 15°C or less.

[0050] The second polyester elastomer preferably has a hard segment content of 50% to 75% by mass. The second polyester elastomer preferably has a crystallization temperature of 30°C to 70°C and a crystallization heat of 8 mJ / mg to 25 mJ / mg.

[0051] The crystallization temperature and heat of crystallization of the resin composition constituting polyester elastomers and bead foam molded articles are measured in accordance with JIS K7121:1987, 2012 "Method for measuring transition temperature of plastics" and JIS K7122:1987, 2012 "Method for measuring transition heat of plastics".

[0052] However, the sampling method and temperature conditions shall be measured as follows. Using a differential scanning calorimeter (DSC6220 ASD-2, manufactured by SII Nanotechnology Co., Ltd. or DSC7000X AS-3, manufactured by Hitachi High-Tech Science Co., Ltd.), approximately 6 mg of the sample was packed tightly into the bottom of an aluminum measuring container. Under a nitrogen gas flow rate of 20 mL / min, the temperature was lowered from 30°C to -70°C, held for 10 minutes, then heated from -70°C to 220°C (1st Heating), held for 10 minutes, then lowered from 220°C to -70°C (Cooling), held for 10 minutes, and then heated from -70°C to 220°C (2nd Heating) to obtain the DSC curve. The crystallization temperature is determined as the cooling crystallization peak temperature. The cooling crystallization peak temperature is determined by using the analysis software provided with the instrument to read the top temperature of the highest-temperature crystallization peak observed during the cooling process. Then, using the analysis software provided with the device, the point where the DSC curve deviates from the high-temperature baseline (the point where the differential curve (DDSC) changes from a horizontal straight line to a curved shape) and the point where the DSC curve returns to the low-temperature baseline (the point where the differential curve (DDSC) returns to a horizontal straight line) are determined, and these are designated as the cooling crystallization start temperature and cooling crystallization end temperature, respectively. The amount of heat for crystallization is then calculated from the area enclosed by the straight line connecting the point at the cooling crystallization start temperature and the point at the cooling crystallization end temperature on the DSC curve, and the DSC curve itself.

[0053] The resin composition may contain additive components in addition to the resin components described above. Additives may include, for example, foam regulators, flame retardants, colorants, antistatic agents, spreading agents, crosslinking agents, fillers, lubricants, etc. The proportion of additive components in the resin composition is greater than 0% by mass and less than or equal to 10% by mass. The proportion of additive components in the resin composition may be 5% by mass or less, or 2% by mass or less.

[0054] Bead foam molded articles can be manufactured, for example, by preparing non-foamed resin particles with the above-mentioned resin composition, incorporating a foaming agent into the resin particles to make foamed resin particles, foaming the foamed resin particles to obtain polyester elastomer foam particles, and then molding the polyester elastomer foam particles in a mold.

[0055] (Resin particles) The shape of the resin particles is not particularly limited and can be spherical, ellipsoidal (egg-shaped), cylindrical, prismatic, pellet-shaped, or granular. The resin particles may be made using the raw material pellets as they are, or they may be repelled to any size and shape. The resin particles may have a length of 0.5 to 5.5 mm and an average diameter of 0.5 to 5.5 mm. If the length is less than 0.5 mm and the average diameter is less than 0.5 mm, the gas retention capacity will be low when the resin particles are foamed, making foaming difficult. If the length is greater than 5 mm and the average diameter is greater than 5 mm, when foamed, heat may not be transferred to the inside, which may result in a core forming in the polyester elastomer foam particles. Such resin particles can be produced by extruding them into a string shape using an extruder and cutting them to a predetermined size.

[0056] The length L and average diameter D of the resin particles are measured using calipers as follows: Length L is the length of the resin particles in the extrusion direction during pelletization, and average diameter D is the average of the minimum diameter and maximum diameter of the resin particles in the direction perpendicular to the extrusion direction. If the raw material pellets are used as is, length L is the longest diameter of the resin particles, and average diameter D is the average of the minimum and maximum diameters in the direction perpendicular to this diameter.

[0057] (Method for manufacturing foamed resin particles) Foamable resin particles can be obtained through a process (impregnation process) in which a foaming agent is impregnated into resin particles. The foaming agent may be an organic gas or an inorganic gas. Examples of inorganic gases include air, nitrogen, and carbon dioxide. Examples of organic gases include hydrocarbons such as propane, butane, and pentane, and fluorine-based foaming agents. Only one type of foaming agent may be used, or two or more types may be used in combination.

[0058] The amount of foaming agent contained in the resin particles may be 1 to 30 parts by mass per 100 parts by mass of resin contained in the resin particles. If the amount is less than 1 part by mass, the foaming power will be low, making it difficult to foam properly. If the amount of foaming agent exceeds 30 parts by mass, the bubble film is more likely to break, the plasticizing effect will be too large, the viscosity during foaming will tend to decrease, and shrinkage will be more likely. The amount of physical foaming agent may be 5 to 12 parts by mass. Within this range, the foaming power can be sufficiently increased, and foaming can be performed even more effectively.

[0059] Known methods can be used to impregnate resin particles with a physical foaming agent. Examples include wet impregnation and dry impregnation. In the wet impregnation method, resin particles, a dispersant, and water are supplied to an autoclave and stirred to disperse the resin particles in water and produce a dispersion. A foaming agent is then injected under pressure into this dispersion to impregnate the resin particles with the foaming agent. In the dry impregnation method, a foaming agent is injected under pressure into the resin particles in the autoclave to impregnate the resin particles with the foaming agent.

[0060] The dispersant is not particularly limited and can be poorly water-soluble inorganic substances such as calcium phosphate, magnesium pyrophosphate, sodium pyrophosphate, and magnesium oxide, or surfactants such as sodium dodecylbenzenesulfonate. If the impregnation temperature of the physical foaming agent into the resin particles is low, the time required for the physical foaming agent to impregnate the resin particles will be long, which may reduce production efficiency. If it is high, the resin particles may fuse together and form bonded particles. The impregnation temperature may be -20 to 120°C, 0 to 120°C, 20 to 120°C, or 40 to 120°C.

[0061] Foaming aids (plasticizers) and foam regulators may be used in combination with physical foaming agents. Examples of foaming aids (plasticizers) include diisobutyl adipate, toluene, cyclohexane, and ethylbenzene.

[0062] Examples of foam regulators include higher fatty acid amides, higher fatty acid bisamides, higher fatty acid salts, and inorganic foam nucleating agents. Multiple types of these foam regulators may be combined. Examples of higher fatty acid amides include stearic acid amide and 12-hydroxystearic acid amide. Examples of higher fatty acid bisamides include ethylenebisstearate amide and methylenebisstearate amide. An example of a higher fatty acid salt is calcium stearate. Examples of inorganic foam nucleating agents include talc, calcium silicate, and synthetic or naturally occurring silicon dioxide. In addition to the above, foam regulators that also function as chemical foaming agents may be used. Examples of such foam regulators include sodium bicarbonate, citric acid, sodium bicarbonate, azodicarbonamide, dinitrosopentamethylenetetramine, benzenesulfonyl hydrazide, and hydrazodicarbonamide.

[0063] The content of the bubble regulator may be 0.05 to 2 parts by mass or 0.01 to 1.5 parts by mass per 100 parts by mass of foamed resin particles. If the amount of bubble regulator is less than 0.05 parts by mass, it may become difficult to control the bubble diameter. If the amount of bubble regulator is more than 2 parts by mass, the resin properties may change, for example, a decrease in the strength of the molded article may occur.

[0064] (Method for manufacturing polyester elastomer foam particles) Polyester elastomer foam particles can be obtained through a foaming process (foaming step) of foamable resin particles. The concentration of polyester elastomer foam particles is 0.015~0.2 g / cm³. 3 It may have a bulk density in the range of 0.015 g / cm³. 3 If the size is smaller, shrinkage may occur in the resulting foamed bead molded product, resulting in an unsatisfactory appearance and a decrease in the mechanical strength of the foamed bead molded product. 0.2 g / cm 3 If the particles are larger, the lightweight properties of the foamed bead product may decrease. The shape of the polyester elastomer foam particles is not particularly limited and may include spherical, ellipsoidal (egg-shaped), cylindrical, prismatic, pellet-like, or granular shapes.

[0065] Polyester elastomer foam particles may have an average particle diameter of 1 to 15 mm. If the average particle diameter is less than 1 mm, the manufacturing of the polyester elastomer foam particles themselves may be difficult and the manufacturing cost may increase. If it is greater than 15 mm, the ability to fill the mold may decrease when producing a bead foam molded body by in-mold molding. Here, the average particle diameter of polyester elastomer foam particles (excluding the average particle diameter of polyester elastomer foam particles in the fused body) refers to the average value calculated by measuring the maximum and minimum diameters of 20 polyester elastomer foam particles and dividing them by "(maximum value + minimum value) ÷ 2".

[0066] In the foaming process, the foaming temperature and heating medium are not particularly limited, as long as foamable resin particles are foamed to obtain polyester elastomer foam particles. Alternatively, polyester elastomer foam particles may be produced by methods such as supplying resin particles, water, a dispersant and a foaming agent to an autoclave, heating to impregnate the resin particles with the foaming agent, and then releasing them from the autoclave under low pressure (release foaming), or supplying a base resin and a foaming agent to an extruder, melting and kneading them, and then extruding them under lower pressure than inside the extruder to foam and cut them (extrusion foaming).

[0067] A bead-foamed molded body can be manufactured by a molding process in which polyester elastomer foam particles contained in a mold are heated to cause secondary foaming (volume expansion) of the polyester elastomer foam particles, and the polyester elastomer foam particles are fused together to impart a shape corresponding to the molding space of the mold. A step of applying internal pressure as needed before subjecting the polyester elastomer foam particles to in-mold molding may also be included.

[0068] Polyester elastomer foam particles in the foam may have an average particle size of 1 to 15 mm. Thank you for creating this. Due to internal company circumstances, we will be changing the material information as follows. • We have been informed that Perprene GP-xxx is not the official product name, so we will correct it. • The hard segment configuration of Perplen may cause problems with other companies, and will be corrected. Here, the average particle diameter refers to the average value calculated by measuring the maximum and minimum diameters of 20 polyester elastomer foam particles in their cross-section, and dividing the result by (maximum value + minimum value) ÷ 2. The average particle diameter can be 1 mm, 3 mm, 5 mm, 7 mm, 10 mm, 12 mm, or 15 mm.

[0069] Bead foam molded products are suitable for use as cushioning materials in various applications due to their excellent lightness, strength, and rebound modulus. These cushioning materials can be used in sports equipment (cushioning materials attached to protective fences, goalposts and other support structures, ski lift towers, etc.; interior materials for helmets in motorsports, American football, and ice hockey; boxing punching mitts and headgear; protectors for baseball catchers, referees, and ice hockey goalkeepers; shoe insoles and sports shoe midsoles; yoga mats and household cushioning mats, etc.).

[0070] The above is merely a limited example of the present invention, and the present invention is not limited in any way to the above example. The above discloses the following invention.

[0071] [1] It is composed of multiple foamed resin particles that are fused together with each other. A bead foam molded article in which the foamed resin particles are polyester elastomer foam particles composed of a resin composition containing a polyester elastomer, Density is 200 kg / m³ 3 Below, With a rebound modulus of 70% or more, The tear strength is 2.0 N / mm or higher. The aforementioned resin composition, A bead foam molded article in which, when the temperature dependence of the storage modulus is represented on a semi-logarithmic graph with the vertical axis representing the logarithmic scale of storage modulus (Pa) and the horizontal axis representing temperature (°C), the decrease in the storage modulus per unit temperature is 0.06 or more at a first temperature (T1) between 120°C and 140°C, the decrease in the storage modulus per unit temperature returns to 0.06 or less at a second temperature (T2) between 140°C and 170°C, and the temperature difference (ΔT(T2-T1)) between the first temperature (T1) and the second temperature (T2) is greater than 17°C and less than or equal to 35°C.

[0072] [2] A bead foam molded article as described in [1], wherein the Asker C hardness is 40 or less.

[0073] [3] The bead foam molded article according to [1] or [2], wherein the fusion rate between the polyester elastomer foam particles is 70% or more.

[0074] [4] A buffer composed of at least a portion of a bead foam molded body, A buffer body in which the bead foam molded body is the bead foam molded body described in any of [1] to [3]. [Examples]

[0075] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0076] <Example 1> • Resin particles 70 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 30 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0077] (2) Foamed resin particles In a 5L autoclave equipped with a stirrer, 1.5 kg (100 parts by mass) of resin particles, 3 L of distilled water, and 4 g of surfactant (linear alkylbenzene sulfonate sodium, trade name: "Newlex R", manufactured by Yuka Sangyo Co., Ltd.) were added. After sealing the autoclave, 16 parts by mass of the foaming agent butane (n-butane:isobutane = 7:3) were injected under pressure while stirring. Next, the autoclave was heated at 70°C for 2 hours and then cooled to 25°C. After cooling was complete, the autoclave was depressurized, the surfactant was immediately washed off with distilled water, and dewatering was performed to obtain foaming resin particles. The amount of impregnated gas in the foaming resin particles was 6.6% by mass.

[0078] (3) Polyester-based elastomer foam particles 100 parts by mass (1.5 kg) of foamed resin particles were coated with 0.25 parts by mass of an anti-adhesion agent (polyoxyethylene polyoxypropylene glycol, trade name: "Epan 450", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and then placed into a cylindrical pre-foaming machine with a stirrer with an internal volume of 50 L. The mixture was heated with steam at a gauge pressure of 0.12 MPa while stirring to obtain polyester elastomer foamed particles.

[0079] (4) Bead foam molded body Polyester elastomer foam particles were placed in an autoclave, nitrogen gas at a gauge pressure of 0.3 MPa was injected, and the autoclave was left to stand at 30°C for 18 hours to impregnate the polyester elastomer foam particles with compressed air (internal pressure was applied). The amount of nitrogen gas impregnated was 0.9% by mass. Polyester elastomer foam particles were removed from the autoclave and immediately filled into a molding cavity measuring 400 mm x 300 mm x 20 mm thick with steam vents. Heat molding was then performed with steam at a gauge pressure of 0.21 MPa to obtain a bead foam molded body.

[0080] <Example 2> (1) Resin particles 80 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 20 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0081] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Example 1.

[0082] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Example 1.

[0083] <Example 3> (1) Resin particles 90 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 10 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFE", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0084] (2) Polyester-based elastomer foam particles

[0085] Polyester-based elastomer foam particles were obtained using the same method as in Example 1. (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Example 1.

[0086] <Example 4> (1) Resin particles 70 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 30 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), a polyester elastomer resin masterbatch of diketopyrrolopyrrole (DPP) as a pigment (constituent resin: "Perprene P-75M", pigment concentration 10% by mass, manufactured by Saika Chemical Co., Ltd.), and 0.3 parts by mass of organic foam regulator (ethylenebis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (with 8 nozzles, each 1.3 mm in diameter) attached to the front end of a single-screw extruder and cut in water at 30-50°C. The resulting resin particles had a particle length L of 1.4-1.8 mm and an average particle diameter D of 1.4-1.8 mm.

[0087] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Example 1.

[0088] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Example 1.

[0089] <Example 5> A bead foam molded body was obtained in the same manner as in Example 4, except that the pigment was changed to a copper phthalocyanine polyester elastomer resin masterbatch (constituent resin: "Perprene P-75M", pigment concentration 10% by mass, manufactured by Saika Chemical Co., Ltd.).

[0090] <Example 6> A bead foam molded body was obtained in the same manner as in Example 4, except that the pigment was changed to a carbon black polyester elastomer resin masterbatch (constituent resin: "Perprene P-75M", pigment concentration 10% by mass, manufactured by Saika Chemical Co., Ltd.).

[0091] <Example 7> A bead foam molded article was obtained in the same manner as in Example 1, except that it contained 1 part by mass of talc per 100 parts by mass of polyester elastomer.

[0092] <Comparative Example 1> (1) Resin particles 100 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether) and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The resulting resin particles had a particle length L of 1.4-1.8 mm and an average particle diameter D of 1.4-1.8 mm.

[0093] (2) Foamed resin particles In a 5L autoclave equipped with a stirrer, 1.5 kg (100 parts by mass) of resin particles, 3 L of distilled water, and 4 g of surfactant (linear alkylbenzene sulfonate sodium, trade name: "Newlex R", manufactured by Yuka Sangyo Co., Ltd.) were added. After sealing the autoclave, 16 parts by mass of the foaming agent butane (n-butane:isobutane = 7:3) were injected under pressure while stirring. Next, the autoclave was heated at 70°C for 2 hours and then cooled to 25°C. After cooling was complete, the autoclave was depressurized, the surfactant was immediately washed off with distilled water, and dewatering was performed to obtain foaming resin particles. The amount of impregnated gas in the foaming resin particles was 6.6% by mass.

[0094] (3) Polyester-based elastomer foam particles 1.5 kg (100 parts by mass) of foamed resin particles were coated with 0.25 parts by mass of an anti-adhesion agent (polyoxyethylene polyoxypropylene glycol, product name: "Epan 450", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and then placed into a cylindrical pre-foaming machine with a stirrer with an internal volume of 50 L. The mixture was heated with steam at a gauge pressure of 0.12 MPa while stirring to obtain polyester elastomer foamed particles.

[0095] (4) Bead foam molded body Polyester elastomer foam particles were placed in an autoclave, and nitrogen gas at a gauge pressure of 0.3 MPa was injected. The autoclave was then left to stand at 30°C for 18 hours to impregnate the polyester elastomer foam particles with nitrogen gas (internal pressure was applied). The amount of nitrogen gas impregnation was 0.9% by mass. Polyester elastomer foam particles were removed from the autoclave and immediately filled into a molding cavity measuring 400 mm x 300 mm x 20 mm thick with steam vents. Heat molding was then performed with steam at a gauge pressure of 0.21 MPa to obtain a bead foam molded body.

[0096] <Comparative Example 2> (1) Resin particles 20 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 80 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0097] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0098] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0099] <Comparative Example 3> (1) Resin particles 40 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 60 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0100] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0101] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0102] <Comparative Example 4> (1) Resin particles 100 parts by mass of polyester elastomer (product name: "Perprene P-40H", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether) and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The resulting resin particles had a particle length L of 1.4-1.8 mm and an average particle diameter D of 1.4-1.8 mm.

[0103] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0104] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0105] <Comparative Example 5> (1) Resin particles 40 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 60 parts by mass of polyester elastomer (product name: "Perprene P-150M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0106] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0107] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0108] <Comparative Example 6> (1) Resin particles 55 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 45 parts by mass of polyester elastomer (product name: "Perprene P-150M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0109] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0110] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0111] <Comparative Example 7> (1) Resin particles 85 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 15 parts by mass of polyester elastomer (product name: "Perprene P-150M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0112] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0113] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0114] <Comparative Example 8> (1) Resin particles 55 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 45 parts by mass of polyester elastomer (product name: "Perprene P-55B", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0115] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0116] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0117] <Comparative Example 9> (1) Resin particles 85 parts by mass of polyester elastomer (product name: "Perprene P-75M", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), 15 parts by mass of polyester elastomer (product name: "Perprene P-55B", manufactured by Toyobo Co., Ltd., hard segment: polybutylene terephthalate, soft segment: aliphatic polyether), and 0.3 parts by mass of organic foam regulator (ethylene bis-stearamide, product name: "Kao Wax EBFF", manufactured by Kao Corporation) were supplied to a single-screw extruder and melt-kneaded at 180-280°C. Next, the molten polyester elastomer was cooled to adjust its viscosity, and then the resin was extruded from each nozzle of a multi-nozzle mold (having 8 nozzles with a diameter of 1.3 mm) attached to the front end of the single-screw extruder and cut in water at 30-50°C. The obtained resin particles had a particle length L of 1.4 to 1.8 mm and an average particle diameter D of 1.4 to 1.8 mm.

[0118] (2) Polyester-based elastomer foam particles Polyester-based elastomer foam particles were obtained using the same method as in Comparative Example 1.

[0119] (3) Bead foam molded body A bead foam molded body was obtained using the same method as in Comparative Example 1.

[0120] For each example and comparative example, the bulk density of the polyester elastomer foam particles, the density of the bead foam molded body, the rebound modulus, the tear strength, the fusion rate, the surface hardness (Asker C hardness), the first temperature (T1:°C), the second temperature (°C), and the temperature difference between the second and first temperatures (T2-T1) were determined. The results are shown in Tables 1 and 2 below. Furthermore, Figure 3 shows the relationship between temperature and storage modulus for samples taken from the bead foam molded bodies of Example 1 and Comparative Example 1, plotted on a semi-logarithmic graph with the vertical axis representing the storage modulus on a logarithmic scale and the horizontal axis representing temperature.

[0121] [Table 1]

[0122] [Table 2]

[0123] As shown above, compared to the comparative example, the temperature difference between the second temperature and the first temperature is larger in the example, and a bead foam molded article is obtained that exhibits a high rebound modulus even at low density, and has excellent fusion rate and tear strength. From this, it can be understood that the present invention provides a bead foam molded body that is composed of polyester elastomer foam particles while possessing both lightness and excellent strength and rebound elasticity, and that the present invention provides a cushioning material made of polyester elastomer that is excellent in lightness, strength and rebound elasticity. [Explanation of Symbols]

[0124] CV: Curve of change of storage modulus with temperature CV CV1: High decrease interval (the interval in which the decrease in storage modulus due to temperature is large) CV2: Low-decrease interval (interval where the decrease in storage modulus due to temperature is small), CV21: First low-decrease interval, CV22: Second low-decrease interval

Claims

1. It is composed of multiple foamed resin particles that are fused together with each other. A bead foam molded article in which the foamed resin particles are polyester elastomer foam particles composed of a resin composition containing a polyester elastomer, Density of 200 kg / m³ 3 Below, With a rebound modulus of 70% or more, The tear strength is 2.0 N / mm or higher. The aforementioned resin composition, A bead foam molded article in which, when the temperature dependence of the storage modulus is represented on a semi-logarithmic graph with the vertical axis on a logarithmic scale of the storage modulus (Pa) and the horizontal axis on temperature (°C), the decrease in the storage modulus per unit temperature is 0.06 or more at a first temperature (T1) between 120°C and 140°C, the decrease in the storage modulus per unit temperature returns to 0.06 or less at a second temperature (T2) between 140°C and 170°C, and the temperature difference (ΔT(T2-T1)) between the first temperature (T1) and the second temperature (T2) is greater than 17°C and less than or equal to 35°C.

2. The bead foam molded article according to claim 1, wherein the Asker C hardness is 40 or less.

3. The bead foam molded article according to claim 1 or 2, wherein the fusion rate between the polyester elastomer foam particles is 70% or more.

4. A buffer composed of at least a portion of a bead foam molded body, A buffer body wherein the bead foam molded body is the bead foam molded body according to claim 1 or 2.

Citation Information

Patent Citations

  • Molded foam of ester-based elastomer, uses thereof, and expanded beads of ester-based elastomer

    WO2018012089A1